2022
DOI: 10.3389/fmicb.2022.941734
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization and in vitro fungicide screenings of a new causal agent of wheat Fusarium head blight in Tibet, China

Abstract: Wheat (Triticum aestivum L.) is an important cereal crop, widely grown throughout the temperate zones, and also suitable for cultivation at higher elevations. Fusarium head blight (FHB) is a highly destructive disease of wheat throughout the globe. In July 2020, serious wheat FHB symptoms were observed in open fields located in Linzhi City, southeast of Tibet, China. The causal agent was identified as Fusarium avenaceum (Fr.) Sacc. by amplification and sequencing of the internal transcribed spacer (ITS) region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…In this study, mycelia of F. commune grew in all the carbon sources tested, and the fastest growth was observed in the medium with soluble starch as a carbon source. Similar to our findings, F. avenaceum and F. graminearum were reported to grow fastest in medium with soluble starch as a carbon source (Chen, Ran, et al., 2022; Tang et al., 2022). For oomycete plant pathogens, the types of carbohydrates used as an energy source may influence the production, liberation and germination of zoospores outside the root and oospore formation inside the root (Papavizas & Ayers, 1964).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, mycelia of F. commune grew in all the carbon sources tested, and the fastest growth was observed in the medium with soluble starch as a carbon source. Similar to our findings, F. avenaceum and F. graminearum were reported to grow fastest in medium with soluble starch as a carbon source (Chen, Ran, et al., 2022; Tang et al., 2022). For oomycete plant pathogens, the types of carbohydrates used as an energy source may influence the production, liberation and germination of zoospores outside the root and oospore formation inside the root (Papavizas & Ayers, 1964).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that that F. oxysporum hyphae can grow under alternating light and dark periods (Shao et al, 2014). Tang et al (2022) found that an alternating cycle of 8 h of light and 16 h of dark is beneficial for the growth of F. avenaceum hyphae. However, Costa et al (2021) did not observe a significant difference in the germination and growth of F. fujikuroi under different light and dark conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, mycelia grew in all the carbon sources tested, and the fastest growth was observed in the medium with soluble starch as a carbon source. Similar to our findings, Fusarium avenaceum and F. graminearum were reported to grow fastest in medium with soluble starch as a carbon source (Tang et al 2022;Chen et al 2022b). The types of carbohydrates used as an energy source may influence the production, liberation, and germination of zoospores outside the root and oospore formation inside the root (Papavizas and Ayers 1964).…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest the importance of considering photoperiod as a factor in the development of management strategies for Fusarium related plant diseases. Chemical fungicides are commonly used as the main control measure for plant pathogens (Tang et al 2022;Chen et al 2022c). However, their improper use can pose safety hazards.…”
Section: Discussionmentioning
confidence: 99%
“…In major crops, productivity losses due to different kinds of plant diseases range from 21% to 31% worldwide [ 1 ]. In addition, many plant pathogens have developed resistance to different chemical pesticides [ 2 ]. Consequently, it has become difficult to control certain plant diseases due to the paucity of efficient compounds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%